Penta Helix Collaboration for Sustainable Tourism in Tutuala, Timor Leste - Fatima, Arlindo Do Ceo; Winarno, Agung; Pratikto, Heri (Green Publisher, 2024)
Penta Helix collaboration is an important approach in developing sustainable tourism destinations, especially in areas where natural and cultural tourism potential is not yet optimal, such as Tutuala, Lautem, and Timor Leste Districts. This study aims to identify, analyze, and systematize literature related to the role of Penta Helix—which includes government, academics, business, communities, and media—in supporting sustainable tourism development in the region. Using the Systematic Literature Review (SLR) method, this article examines various previous studies to map cross-sector collaboration in increasing tourist attractions and their impacts on environmental, social, and economic sustainability. The results of the study show that the active involvement of each Penta Helix element is very influential in strengthening destination governance (Dredge & Jenkins, 2019; Yusran et al., 2020), expanding the tourism market (Sigala, 2020; Truong & Hall, 2021), and improving the quality of life of local communities (Goodwin, 2019; Cruz et al., 2021). However, challenges related to coordination between stakeholders and limited resources are still major obstacles in implementing this collaborative strategy (Jamal & Stronza, 2019). Therefore, stronger synergy efforts are needed, as well as the role of the media in promoting tourism potential and raising awareness of the importance of sustainability in tourism.